VD_FINDINFO HC / 2009 / 440 vom 26. Oktober 2009 - VD Tribunal cantonal (2009)
NOTAIRE, CERTIFICAT DE CAPACITÉ, MODÉRATION, COMMUNAUTÉ HÉRÉDITAIRE, COMPÉTENCE, HONORAIRES | 602 CC, 120 al. 3 LNo, 28 LNo